2023
DOI: 10.1101/2023.02.13.23285854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hacking Acute Care: A Qualitative Study on the Healthcare Impacts of Ransomware Attacks Against Hospitals

Abstract: Background and objectives: Cyberattacks against healthcare institutions are an increasing threat and have the potential to impair health outcomes. Current research is limited and focuses mainly on the technical consequences, whereas little is known about the healthcare staff experiences and the impact on emergency care, both during the incident and in the recovery phase. This study aims to explore the impact of a sample of large ransomware attacks against hospitals between 2017 and 2022 on acute care delivery … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Although it is unknown whether this also represents better preparedness, several studies have shown that cybersecurity in hospitals can be significantly improved. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether this also represents better preparedness, several studies have shown that cybersecurity in hospitals can be significantly improved. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…Even critical life-saving devices, such as pacemakers and insulin pumps, have been demonstrated to be vulnerable to attacks [20], [103]. The fragility of our technology also provided the conditions to allow ransomware attacks on hospitals and electrical companies which have put countless lives at risk [136], [199].…”
Section: Introductionmentioning
confidence: 99%